Określanie miąższości i zagęszczenia drzew w drzewostanach centralnej Polski na podstawie danych lotniczego skanowania laserowego w dwufazowej metodzie inwentaryzacji zasobów drzewnych - Miścicki, Stanisław; Stereńczak, Krzysztof (Leśne Prace Badawcze, 2013)
This paper describes a method of determining the stocking density and volume of forest stands based on airborne laser-scanning data. The aim of this study was to determine the relationship between ground-based measurements of standing volume and tree-density, and those acquired based on the Crown Height Model (CHM) interpolated from airborne laser-scanning data. Data were collected from 34 sample plots of two sizes for the CHM analysis: 500 m 2 (radius 12.61 m) and 1963.5 m 2 (radius of 25.0 m): Trees for sampling were selected using two methods, those whose „centroid” was fully within the sample plot (the tree was considered to be within the sample plot if the centroid of the crown was inside the circle) and those at the „border” (the tree was included in the sample plot if, at least, one part of the contour of the crown was inside the circle). There was a strong relationship (R 2 = 0.86) between standing volume measured in sample plots on the ground and the indices produced by the crown elevation model at the locations where the ground-based measurements were performed.